2016
DOI: 10.1103/physrevb.93.155418
|View full text |Cite
|
Sign up to set email alerts
|

Upconverted photoluminescence induced by radiative coupling between excitons

Abstract: We propose an unconventional scheme of photoluminescence in a semiconductor thin film, where the nonlocal correlation between an excitonic wave and a light wave prominently enhances the exciton-light coupling beyond the long-wavelength approximation (the so-called excitonic superradiance regime). On the basis of the developed method extending input-output theory, we elucidate atypical photoluminescence effects due to the strong wave-wave correlation. In particular, the upconverted photoluminescence based on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There exist examples of systems with magnetic phase transitions of the type ferromagnet-incommensurate order: MnP with orthorhombic (distorted hexagonal) lattice, the wave vector of the incommensurate phase being directed along the x axis [8][9][10]; YbAgGe (the lattice is hexagonal noncentrosymmetric, the wave vectors are (1/3, 0, 1/3) → (0, 0, 0.324) [37,39,40]; CePtAl (orthorhombic crystal lattice, magnetic order is a superposition of ferromagnetic and incommensurate order with Q = (0, 0.463(8), 0), and of commensurate AFM order with Q = (0, 0.5, 0)) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist examples of systems with magnetic phase transitions of the type ferromagnet-incommensurate order: MnP with orthorhombic (distorted hexagonal) lattice, the wave vector of the incommensurate phase being directed along the x axis [8][9][10]; YbAgGe (the lattice is hexagonal noncentrosymmetric, the wave vectors are (1/3, 0, 1/3) → (0, 0, 0.324) [37,39,40]; CePtAl (orthorhombic crystal lattice, magnetic order is a superposition of ferromagnetic and incommensurate order with Q = (0, 0.463(8), 0), and of commensurate AFM order with Q = (0, 0.5, 0)) [32].…”
Section: Discussionmentioning
confidence: 99%
“…This situation is typical, besides a number of rare earth compounds, for many compounds of transition metals, such as manganese and chromium, whose atoms in the free state have a large moment which is mainly preserved in the metallic state. In manganese phosphide MnP, there is a competition between the helical and ferromagnetic orders, and the phase transition between them occurs under pressure increase [8][9][10]. A completely different situation occurs for CrAs 1−x Sb x , where there is a competition of AFM and incommensurate (spiral, order of the 'double helix' type) magnetic order, and the phase transition between them occurs at x ∼ 0.5 [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We developed the LiOF theory, which referred to the PL theory of excitons in solids [13] and the optical force theory derived from Maxwell's stress tensor [14]. The Hamiltonian considers a coupled system of excitons and radiation fields.…”
Section: Theorymentioning
confidence: 99%
“…Imada et al reported that it is possible to probe and control the individual state of a single molecule owing to the high space and energy resolution resulting from measuring the photoluminescence spectrum of a single phthalocyanine using a scanning tunneling microscope and tunable laser [2]. In this study, based on the nonlocal theory and input-output theory [3], we propose the theory that allows us to discuss the optical information obtained from not only the optical response of the molecule but also the parameters of the incident field, the position where photoluminescence is observed, and the shape of the probe.…”
Section: Introductionmentioning
confidence: 97%